Large deletions and splicing‐site mutations in the STK11 gene in Peutz‐Jeghers Chilean families. (7th August 2012) - Orellana, P; López‐Köstner, F; Heine, C; Suazo, C; Pinto, E; Church, J; Carvallo, P; Alvarez, K
<x xml:space="preserve">Abstract</x> Peutz‐Jeghers syndrome (PJS) is an autosomal dominant disorder characterized by mucocutaneous melanocytic macules, gastrointestinal hamartomatous polyposis and an increased risk of various neoplasms. Germline mutations in the serine/threonine kinase 11 (STK11) gene have been identified as a cause for PJS. The aim of this study was to characterize the genotype of Chilean PJS patients. Mutation screening of 13 patients from eight PJS families was performed using a single strand conformation polymorphism analysis, DNA sequencing and multiplex ligation‐dependent probe amplification assay. The breakpoints of the genomic rearrangements were assessed by a long‐range polymerase chain reaction and sequencing. The results revealed the existence of seven different pathogenic mutations in STK11 gene in seven unrelated families, including three point mutations and four large genomic deletions. Three of these point mutations (43%, 3/7) may be considered as novel. Our results showed that a germline mutation is present in STK11 in 88% of probands fulfilling the diagnostic criteria of PJS. In this study, the combination of two different experimental approaches in the screening of the STK11 in PJS, led to a higher percentage of mutation detection.